2022
DOI: 10.1093/brain/awac045
|View full text |Cite
|
Sign up to set email alerts
|

Widespread white matter oedema in subacute COVID-19 patients with neurological symptoms

Abstract: While neuropathological examinations in patients who died from COVID-19 revealed inflammatory changes in cerebral white matter, cerebral MRI frequently fails to detect abnormalities even in the presence of neurological symptoms. Application of multi-compartment diffusion microstructure imaging (DMI), that detects even small volume shifts between the compartments (intra-axonal, extra-axonal and free water/CSF) of a white matter model, is a promising approach to overcome this discrepancy. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 55 publications
6
44
1
Order By: Relevance
“…Our DMI approach further considers an additional free fluid compartment (V-ISO). In a previous study, our DMI approach was reported to be highly sensitive to discrete shifts of microstructural compartments otherwise not detectable on conventional MRI [19]. DMI was also more sensitive in detecting pathological changes in brain tissue in the context of neurodegeneration than DTI [18].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Our DMI approach further considers an additional free fluid compartment (V-ISO). In a previous study, our DMI approach was reported to be highly sensitive to discrete shifts of microstructural compartments otherwise not detectable on conventional MRI [19]. DMI was also more sensitive in detecting pathological changes in brain tissue in the context of neurodegeneration than DTI [18].…”
Section: Discussionmentioning
confidence: 86%
“…The arm was positioned in neutral zero position. For chemical shift encoding-based water-fat separation of the RC, a transverse-prescribed two-point T1w Dixon sequence was acquired with the following parameters: repetition time (TR) = 4.2 ms, echo times (TE) = 1.23 and 2.46 ms, flip angle = 5°, GRAPPA factor = 2, voxel size = 0.7 × 0.7 × 3.0 mm 3 , phase encoding direction = A/P, consecutive slices = 48, scan time = 54 s. The dMRI sequence was adapted from the previously published brain-specific sequence [19] to address the specific requirements for dMRI in the musculature [27][28][29] resulting in the following parameters: transverse orientation, 23 consecutive slices, voxel size = 2.0 × 2.0 × 4 mm 3 , TR = 4500 ms, TE = 90 ms, bandwidth = 2222 Hz/Px, GRAPPA factor = 2, 12 diffusion-encoding gradient directions, b-factors = 600 and 1000 s/mm 2 ; scan time = 5:35 min.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes were associated with cognitive impairment and COVID-19-related changes in 18F-FDG PET imaging. 42 Reduced axonal densities have been detected in patients after recovery from COVID-19, 1 year after infection in a sample consisting primarily of hospitalized patients. 43 To our knowledge, there is no serial d-MRI study following up on a non-hospitalized sample of patients with milder COVID-19 forms.…”
Section: [Insert Figure 5 Around Here] 4 Discussionmentioning
confidence: 96%
“…However, FW-corrected DTI measurements are more sensitive to detect changes in some tracts (arcuate and superior longitudinal fascicles). In a recent study, multicompartment diffusion microstructure imaging in inpatients with subacute COVID-19 with neurological symptoms revealed widespread volume shifts compatible with vasogenic edema, affecting various white matter tracts ( 43 ). Redistribution with decreasing intra-axonal and extra-axonal volumes and increasing free water/CSF fraction was observed at a mean follow-up of 30 days ( 43 ).…”
Section: Discussionmentioning
confidence: 99%